Immunities of Officials from Criminal Jurisdiction for International Crimes - A. Yu. Skuratova (Московский журнал международного права, 2009)
The present article covers the actual problems concerning the immunities of individuals in relation to criminal prosecution for international crimes in national and international courts. The immunity is an institute of modern international law. After the World War II the provision that the official capacity does not prevent individuals from criminal proceedings in case of committing international crimes became firmly established and now makes part of modern general international law. At the same time according to international rules high officials, head of states including, enjoy the immunities from criminal jurisdiction. International and domestic court practice in such cases is rather controversial. Thereby the most complicated question is to find the correct correlation between these legal provisions concerning the immunities in case of conductance of international crimes by a high official of a state.